2020
DOI: 10.3389/fsufs.2020.534187
|View full text |Cite
|
Sign up to set email alerts
|

Managing Grazing to Restore Soil Health, Ecosystem Function, and Ecosystem Services

Abstract: uses short-duration grazing periods, long adaptively varied post-grazing plant recovery periods requiring multiple paddocks per herd to ensure adequate residual biomass, and adjustment of animal numbers as environmental and economic conditions change. Using this approach, farmers and ranchers have achieved superior ecosystem and profitability outcomes. This manuscript summarizes the use of AMP grazing as regenerative tool for grazed and rotationally cropped lands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 93 publications
(213 reference statements)
0
73
0
3
Order By: Relevance
“…For example, rewilding might result in woodland expansion on successional habitats, such as heathland and calcareous grassland, which are currently deemed to be of high biodiversity value. It should also be recognised that increases in flows of some ES from agricultural land can be achieved through means other than restoration or rewilding, for example by improved husbandry of crops and livestock, as advocated in approaches such as “regenerative agriculture” and “sustainable intensification” [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, rewilding might result in woodland expansion on successional habitats, such as heathland and calcareous grassland, which are currently deemed to be of high biodiversity value. It should also be recognised that increases in flows of some ES from agricultural land can be achieved through means other than restoration or rewilding, for example by improved husbandry of crops and livestock, as advocated in approaches such as “regenerative agriculture” and “sustainable intensification” [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that RG with few paddocks per herd, longer grazing periods and shorter recovery periods can result in limited plant and animal production advantages compared to continuous set-stocking at low stocking rates (Briske et al, 2008. Low stocking rate as well as improperly applied RG strategies do not facilitate degraded resource recovery or provide adequate economic returns over time (Jakoby et al, 2014(Jakoby et al, , 2015Teague and Kreuter, 2020). Therefore, some grazing research has concluded that there were no improvements in ecological and livestock indicators in RG compared to continuous grazing (CG) and recommended stocking rate adjustment as the primary tool for preventing overgrazing (e.g., Briske et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some grazing research has concluded that there were no improvements in ecological and livestock indicators in RG compared to continuous grazing (CG) and recommended stocking rate adjustment as the primary tool for preventing overgrazing (e.g., Briske et al, 2008). However, grazing management success stories reported at the whole ranch scale are often underpinned by the implementation of adaptive RG strategies (Gerrish, 2004;Provenza et al, 2013;Savory and Butterfield, 2016;Teague and Barnes, 2017;Teague and Kreuter, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The ecosystems in arid and semi-arid lands have suffered several degradation processes in the last decades such as soil and fertility loss, reduction in the forage productivity and changes in the physiognomy of forests, woodlands and rangelands. The degradation causes are due to deforestation, intense and continuous grazing, wildfires, and oscillations in the climatic regimes (McNeely, 2003;Teague and Kreuter, 2020;Chang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%